Metabolic capabilities mute positive response to direct and indirect impacts of warming throughout the soil profile - Nicholas C. Dove; Margaret S. Torn; Stephen C. Hart; Neslihan Taş (Nature Communications, 2021)
There is much uncertainty on the response of soil microbial communities to warming, particularly in the subsoil. Here, the authors investigate microbial community and metabolism response to 4.5 years of whole-profile soil warming, finding depth-dependent effects and elevated subsoil microbial respiration.